The Role of Tenascin-C in Hypertrophic Scar Formation: Insights from Cell and Animal Experiments - Xiang W; Guo Z; Zhang Y; Xu Y (Dove Medical Press, 2024)
Wei Xiang, Zhen Guo, Yiming Zhang, Yuanzhi Xu Department of Stomatology, Shanghai Tenth People's Hospital, School of Medicine, Tongji University, Shanghai, People's Republic of ChinaCorrespondence: Yuanzhi Xu; Yiming Zhang, Email amyxyz01@Hotmail.com; 1701086@tongji.edu.cnBackground: Hypertrophic scars (HS) are dermal diseases characterized by excessive fibroblast proliferation and collagen deposition following burns or trauma. While Tenascin-C (TNC)'s role in promoting visceral fibrosis has been established, its impact on skin tissue fibrosis remains unclear. This study aims to investigate the effects of TNC on HS.Methods: RNA sequence and IHC techniques were used to examine the upregulation of TNC gene in human hypertrophic scar tissue compared to normal tissues. Knockdown of TNC in Human skin fibroblasts (HFF-1) cells was achieved, and expression of Col1 and Col3 was evaluated using qPCR. Sirius red collagen staining assessed impact on total collagen content and ECM deposition. Effects on cell proliferation and migration were investigated through cck-8 and cell scratch experiments. Lentivirus infection was used to knock out TNC, and resulting samples were injected into ear wound of rabbits. Effects of TNC knockout on ear scar formation were measured using digital morphology, ultrasound, SEI, H&E, and Masson trichrome methods.Results: Cell experiments: downregulation of TNC decreased Col1 and Col3 expression, leading to reduced collagen production and extracellular matrix deposition. It did not affect HFF-1 cell proliferation and migration. Animal experiments: TNC knockdown promoted wound healing and reduced collagen deposition in rabbit ears.Conclusion: This study suggests that knocking down TNC inhibits collagen formation and extracellular matrix deposition, thereby inhibiting hypertrophic scar formation. Therefore, TNC can be considered a potential biomarker for HS formation and may offer promising treatment strategies for clinical management of hypertrophic scars.Keywords: Tenascin-C, hypertrophic scars, rabbit ear scar model, HFF-1